Effect of constipation on dosimetry after permanent seed brachytherapy for prostate cancer - Otón, L. Fernando; Dolado, M. Carmen; Núńez, Eduardo J.; Otón, Claudio A. (Journal of Contemporary Brachytherapy, 2015)
Purpose : A major concern in prostate brachytherapy is rectal toxicity, which mainly depends on the dose and volume of rectum involved by radiation. We hypothesize that the rectal distension, as produced by constipation, influences the dosimetric parameters of the rectum and other pelvic organs. Material and methods : An open, controlled, prospective, paired trial (pre-post test) was designed and conducted. Twenty-three patients treated with prostate brachytherapy were recruited, of which 21 were evaluated. All of them underwent two CT scans, the first one with empty rectum and the second with rectum distended by a catheter balloon. Target volumes and organs at risk were delineated, and dosimetric parameters were calculated and then compared for each patient between both CT. Results : For rectum, D2 cc increased 15.8% (p < 0.001) and D 0.1cc 24.05% (p = 0.002) when the rectum was full. A significant difference was also found in dose distribution to prostate, when rectum is distended, a 1% decrease in V100 (p = 0.031) and a 3.25% in D 90 (p = 0.033) was registered. Conclusions : The status of rectal distension, as occurs in constipation, has a deleterious influence on prostate brachytherapy dosimetry. This situation increases the radiation to rectum and modifies dose distribution to prostate. We recommend prevention of constipation for at least two half lives of the radioactive seeds.